2021
DOI: 10.1155/2021/6226291
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Hub Genes and Predicting Target Genes of microRNAs in Tuberculosis via the Bioinformatics Analysis

Abstract: Tuberculosis (TB) is the world's most prevalently infectious disease. Molecular mechanisms behind tuberculosis remain unknown. microRNA (miRNA) is involved in a wide variety of diseases. To validate the significant genes and miRNAs in the current sample, two messenger RNA (mRNA) expression profile datasets and three miRNA expression profile datasets were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed (DE) genes (DEGs) and miRNAs (DE miRNAs) between healthy and TB patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Prior studies have demonstrated that overexpression of THBS1 and THBS2 leads to poor OS in GC patients and has the potential to act as both diagnostic and prognostic biomarkers for GC management [43]. These findings were consistent with Deng et al's [44] studies in another GC cohort.…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies have demonstrated that overexpression of THBS1 and THBS2 leads to poor OS in GC patients and has the potential to act as both diagnostic and prognostic biomarkers for GC management [43]. These findings were consistent with Deng et al's [44] studies in another GC cohort.…”
Section: Discussionsupporting
confidence: 85%
“…We performed KEGG and Gene Ontology (GO) enrichment analyses after compiling the list of hub genes, and the PPI network was then generated. R software “org.Hs.eg.db” was utilized to convert gene symbols into gene IDs, and then “clusterProfiler” was employed to determine significant items with a cutoff criterion ( p < 0.05 and false discovery rate–adjusted p values (FDR) < 0.05) ( Deng et al, 2021 ). We sorted the GO and KEGG pathways by the maximum number of genes and then screened the top ten corresponding items.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, DEGs were imported into the STRING online tool to obtain the protein interaction information. The Cytoscape software MCODE plug-in was utilized to identify the top module with an exact cutoff condition (degree cutoff = 2, node score cutoff = 0.2, k-core = 2, and max depth = 100) ( Deng et al, 2021 ). The overlapping genes of DEGs and hub genes were defined as candidate key genes, determined by the R package “VennDiagram.” In addition, GSE34608 is an external dataset for further expression profile analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These circulating plasma miRNAs can further enable the differential diagnosis of latent and active TB. Diagnostic performance of miRNA can be increased by integrating serum miRNAs with diagnostic models developed by miRNA characteristics and electronic health records (HERs) [61,62] and bioinformatics analysis [63]. Even though miRNA-based detection of TB is convenient in diagnosis in children, the method is challenging to adopt in resource-limited settings.…”
Section: Microrna Detectionmentioning
confidence: 99%